How athletes conceptualise doping, winning, and consequences: insights from using the cognitive interviewing technique with the Goldman dilemma - Woolf, J.; Mazanov, J. (Qualitative Research in Sport, Exercise and Health, 2017)
Theorising on athlete doping has tended to focus on the creation of deductive models. Such models make assumptions on the ways in which athletes conceptualise issues surrounding doping. This is problematic if reality does not match these postulations. While efforts have been made to understand athletes` perspectives on and attitudes towards doping via qualitative research design, there has been little attempt to inductively develop theory on athlete doping. In this study, this deficiency is addressed using the cognitive interviewing technique to understand how athletes conceptualise doping. Cognitive interviewing is typically used to assess question comprehension. However, we used it as a means to dissect how athletes` conceptualise of doping by applying it to variants of a popular thought experiment - the Goldman dilemma. Thirty highly competitive athletes participated in the study and a rich data-set was obtained where athletes described their thoughts and interpretations of doping and related issues. The findings yielded a web of relationship that provides a nuanced account of doping that departs from standard deductive models. The model presented offers a more dynamical account for how athletes think about doping, which has direct implications for anti-doping policy-makers. The outcomes of the study demonstrate the effectiveness of cognitive interviewing as a method that enables inductive theory development on a complex and controversial sport issue.